Introducing Assessment Practice (American International Journal of Sciences and Engineering Research, 2020)
One of the essential beliefs of the education reform is that all students should be literate. Previous studies have shown that every child has a unique competencies and skills. There has been a change in the curriculum and its mode of delivery which will allow the students to have different choices in terms of regional and academies. Different strategies have been established to promote equity and adaptability. This philosophy is to promote four years for the extended which is in line with the nine years education program of the educational reform. This helps to promote equity among the students by improving the quality of teaching and learning.